Bringing Raunkiær with plant architecture: unveiling the climatic drivers of architectural evolution in Euphorbia. Issue 3 (7th June 2021) - Chomicki, Guillaume
Abstract : This article is a Commentary on Anest et al . (2021), 231 : 1278–1295 .